2021
DOI: 10.1007/s11356-021-16773-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the economic development-driven ecological deficit in the EU-15 countries: new evidence from PSTR approach

Abstract: This study empirically analyses the nonlinear impact of economic activities on ecological balance indicators that estimate the balance between economies' pressure on nature and the biologically productive resources areas affected by human activity and the earth's ecological carrying capacity. In measuring this balance, ecological balance sheet indicators are divided into four sub-components; cropland, forest area, fishing grounds and grazing land. The sample of the study consists of the EU-15 countries over th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Policy subjectively guides the economy to transform towards long-term sustainable development, while the market follows its objective laws to gradually eliminate inefficient industries and guide the real economy towards high-quality development. However, their roles in promoting green development will change with the change in the times and objects [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Policy subjectively guides the economy to transform towards long-term sustainable development, while the market follows its objective laws to gradually eliminate inefficient industries and guide the real economy towards high-quality development. However, their roles in promoting green development will change with the change in the times and objects [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourcade and Kluttz ( 2020 ) clarified that digitization helps to realize the ecological modernization of production processes, which can ensure the efficient utilization of resources and the sustainable development of national and global economy. The progress of Internet technology has boosted the resource utilization efficiency and the widespread use of new environmental preservation technologies and elevated the prevention and control of pollutant discharge (Lopez et al 2019 ; Li et al 2021a , b ; Aydin et al 2022 ). Bolla et al ( 2010 ) reported that digital transformation and carbon neutrality are synergistic.…”
Section: Literature Reviewmentioning
confidence: 99%